Data-independent acquisition method for ubiquitinome analysis reveals regulation of circadian biology - Fynn M. Hansen; Maria C. Tanzer; Franziska Brüning; Isabell Bludau; Che Stafford; Brenda A. Schulman; Maria S. Robles; Ozge Karayel; Matthias Mann (Nature Communications, 2021)
Protein ubiquitylation is often studied by proteomics but how data independent acquisition (DIA) may advance these studies remains to be explored. Here, the authors show that DIA improves ubiquitylation site identification and quantification, enabling them to characterize the circadian ubiquitinome in human cells.